Indonesian Language for Java Ethnic: Language and Cultural Problems - Farikah; Mursia Ekawati; Yulia Esti Katrini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The use of Java language for the Java ethnic is influenced by the problems between language acquisition and cultural proprietor. The Java language is the mother tongue for most people of Java. The problem for the Java is a government program that has set Indonesian as the national language. That is the language that will unite and bring interethnic relations, religion and culture in Indonesia. There are other impacts to local languages​​, the Java language is no exception. Javanese people are faced with complex choices about the language and culture as well as educationally and socially. The use of language by government regulation caused the regional languages ​​by the hundreds began somewhat marginalized, especially when the number of speakers slightly. The scope of the use local language to be limitedthat is only used in a family environment for the purposes of religious ceremonies or customs, local cultural events. The limitation scope of the use local language can influence the attitudes of native speakers, as well as for Javanese ethnic and other ethnic groups in Indonesia.